Mindfulness may both moderate and mediate the effect of physical fitness on cardiovascular responses to stress: a speculative hypothesis - Demarzo, Marcelo M.; Montero-Marin, Jesús; Stein, Phyllis K.; Cebolla, Ausiàs; Provinciale, Jaime G.; García-Campayo, Javier (Frontiers in Physiology, 2014)
The psychological construct of mindfulness refers to an awareness that emerges by intentionally paying attention to the present experience in a non-judgmental or evaluative way. This particular quality of awareness has been associated to several indicators of physical and psychological health, and can be developed using mindfulness-based interventions (MBIs), and therefore MBIs have been successfully applied as preventive and complementary interventions and therapies in medicine and psychology. Together with quiet sitting and lying meditation practices, mindful physical exercises such as “mindful walking” and “mindful movement” are key elements in MBIs and couple muscular activity with an internally directed focus, improving interoceptive attention to bodily sensations. In addition, MBIs seem to share similar mechanisms with physical fitness by which they may influence cardiovascular responses to stress. Based on these facts, it is feasible to raise the question of whether physical training itself may induce the development of that particular quality of awareness associated with mindfulness, or if one’s dispositional mindfulness (the tendency to be more mindful in daily life) could moderate the effects of exercise on cardiovascular response to stress. The role of mindfulness as a mediator or moderator of the effect of exercise training on cardiovascular responses to stress has barely been studied. In this study, we have hypothesized pathways (moderation and mediation) by which mindfulness could significantly influence the effects of physical fitness on cardiovascular responses to stress and have discuss potential practical ways to test these hypotheses.